"Click-fluors": triazole-linked saccharide sensors. Issue 8 (14th June 2016) - Zhai, Wenlei; Chapin, Brette M.; Yoshizawa, Akina; Wang, Hui-Chen; Hodge, Stephen A.; James, Tony D.; Anslyn, Eric V.; Fossey, John S.
Abstract : A series of boronic acid-containing saccharide receptors was synthesised via copper catalysed azide–alkyne cycloaddition (CuAAC) reactions. Abstract : A series of boronic acid-containing saccharide receptors was synthesised via copper catalysed azide–alkyne cycloaddition (CuAAC) reactions. Their saccharide binding capacity was studied by 1 H and 11 B NMR spectroscopy titrations and isothermal titration calorimetry (ITC) techniques. Fluorescent sensors were generated by linking a phenylboronic acid (PBA) receptor with fluorophores via a triazole-linker. Fluorescence titrations with fructose revealed that the substitution pattern about the PBA influences the fluorescence response to saccharides. Titrations studied by 1 H NMR spectroscopy suggested that fructose binding is enhanced when the aromatic ring bearing the boronic acid has the triazole-containing substituent at the ortho position. No evidence of either a dative N–B bond or solvent insertion (between B and N) was observed by 11 B NMR spectroscopy. These results demonstrate that synthetic accessible triazole receptors may allow rapid sensor synthesis, screening and discovery.